Plasma Leptin, Nesfatin 1, NPY, and Zinc Levels in Obese and Metabolic Syndrome Children - Aydogdu, Adnan; Unal, Omer; Baltaci, Saltuk Bugra; Menevse, Esma; Mogulkoc, Rasim; Erdem, Said Sami; Buyukinan, Muammer; Baltaci, Abdulkerim Kasim (European Journal of Therapeutics, 2023)
Objective: The aim of this study is to investigate the relationship between leptin, nesfatin 1 and NPY hormones and zinc in boys and girls diagnosed with metabolic syndrome and obesity. Materials and Methods: This study included a total of 6 groups. Group 1 Boy Control, Group 2 Girl Control, Group 3 Obese Boys, Group 4 Obese Girls, Group 5 Boys with Metabolic Syndrome, Group 2 with Girls with Metabolic Syndrome. Plasma leptin, nesfatin-1, NPY (by ELISA method) and serum zinc (by AA method) levels were determined in blood samples obtained from the subjects. Results: Leptin and zinc levels were significantly higher both in boy and girl patients with metabolic syndrome than in obese and control children. Nesfatin-1 and NPY levels were significantly lower both in girl and boy obese and metabolic syndrome children compared to their control groups. Conclusion: In the current study a significant increase in plasma leptin and serum zinc levels and a significant decrease of plasma nesfatin-1 and NPY levels were observed in boys and girls with metabolic syndrome. The findings of our study show that leptin, nesfatin-1 and NPY levels may be important biomarkers in the assessment of metabolic syndrome risk in both girls and boys.